Civil–Military Relations and Human Rights. Issue 3 (July 2022) - Bell, Sam R.; Clay, K. Chad; Kiyani, Ghashia; Murdie, Amanda
Do civil–military relations influence human rights practices? Building on principal–agent theory, we argue that civilian–military relations, instead of having an effect on mean levels of repression, will be associated with the dispersion in human rights practices. States where there is less control of the military or more conflict between civilian and military leadership will see a wider range of human rights practices. We test our hypotheses quantitatively on a global sample of countries, using updated data on civil–military relations and find evidence that civil–military conflict and lack of control increase the variance in human right practices.